Increasing the development level of strength abilities of athletes aged 10-11 in acrobatic rock and roll - Mykhailo Marchenkov; Olena Nasonkina (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to substantiate the effectiveness of the author's program for the development of strength abilities of athletes aged 10-11 engaged in acrobatic rock and roll. Material and methods: the study was conducted in the period from September 2019 to October 2020 on the base of the acrobatic rock and roll club "SUMMIT" in Kharkiv. The study involved 20 young athletes from 10 to 11 years old (10 boys and 10 girls). All studied athletes were engaged in the group of preliminary basic training of the 1st year of training. The following methods were used in the work: analysis and generalization of scientific and methodological literature; pedagogical experiment; methods of mathematical statistics. Results: considering the level of physical fitness of athletes, a training program was developed for the integrated development of strength abilities of young athletes aged 10-11 years, who are engaged in acrobatic rock and roll. The program provided for an increase in the level of development of the strength abilities of the muscles: arms, shoulder girdle, neck, torso, and legs. The introduction of the training program helped to increase the level of development of muscle strength: the upper shoulder girdle by 17.5% in boys and 22% in girls; torso muscles by 12.6% in boys and 10.2% in girls; explosive force of leg muscles by 0.9% in boys and 0.6% of girls. Conclusions: because of the ascertaining experiment with the use of a specially developed training program in young men there was a significant increase of the development strength abilities level of the muscles of the upper shoulder girdle and torso (p <0,05-0,001). As for girls, because of the implementation of the developed training program, the development strength abilities level of the muscles of the upper shoulder girdle significantly increased (p <0.05-0.001).